Barriers to Sport Participation Faced by Ethiopian and Eritrean Migrant Women in Switzerland - Alemu, Betelihem Brehanu; Nagel, Siegfried; Vehmas, Hanna (Italian Sociological Review, 2021)
Global migration (both forced and voluntary) has intensified the interaction between existing and emerging cultures. Sport has gained recognition as an effective tool for enhancing migrants’ overall wellbeing, active participation, and social integration. However, a growing number of studies have shown that migrant women have the lowest rate of sport participation, especially in organized clubs. These findings have brought the accessibility and inclusion of existing sport structure and culture in host countries into question. Using the six-factor model of constraints by Tsai and Coleman (1999), this study explored the barriers that hinder Ethiopian and Eritrea migrant women (EEMW) from participating in sport in Switzerland. Thematic analysis (Braun et al., 2016) was applied to analyze semi-structured interviews and focus group discussions (n=12, 18-51 years old) to understand the interplay between barriers to sport participation and their influence on social integration. The study found that socio-cultural differences from the host community, discrimination, the high cost of sport participation, and structural barriers were influential factors hindering the participation of EEMW. Thus, interactive sport participation among EEMW must be promoted by supportive, multicultural settings to better integrate these women into Swiss society.